Morphometrics Indicates Giant Ordovician Macluritid Gastropods Switched Life Habit During Ontogeny. (September 2014) - Novack-Gottshall, Philip M.; Burton, Keoki
Abstract : Paleontologists have long speculated that the bizarre, giant Ordovician gastropods Maclurites Le Sueur, 1818 and Maclurina Ulrich and Scofield, 1897 lived more like suspension-feeding oysters than typical algivorous snails. Geometric and eigenshape morphometrics demonstrate the plausibility of this lifestyle, but with a twist. The apertures of these gastropods were small ellipsoids when young, transitioning rapidly to polygonal morphologies at maturity, with angulations (sinuses) occurring in regions associated with development of mature ctenidia (gills) and enhanced stability on the seafloor. Combined with knowledge of extant suspension-feeding gastropods and functional and phylogenetic analysis of the anatomy of other fossil relatives, this ontogenetic pattern suggests these snails began life as typical mobile algae-grazers, but switched to sedentary suspension-feeders as they aged.